The detection of pfcrt and pfmdr1 point mutations as molecular markers of chloroquine drug resistance, Pahang, Malaysia - Atroosh, W.M.; Al-Mekhlafi, H.M.; Mahdy, M.A.K.; Surin, J. (BioMed Central, 2012)
Malaria is still a public health problem in Malaysia with chloroquine (CQ) being the first-line drug in the treatment policy of uncomplicated malaria. There is a scarcity in information about the magnitude of Plasmodium falciparum CQ resistance. This study aims to investigate the presence of single point mutations in the P. falciparum chloroquine-resistance transporter gene (pfcrt) at codons 76, 271, 326, 356 and 371 and in P. falciparum multi-drug resistance-1 gene (pfmdr1) at codons 86 and 1246, as molecular markers of CQ resistance